2011
DOI: 10.1038/clpt.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, Safety, and Tolerability of JNJ-38431055, a Novel GPR119 Receptor Agonist and Potential Antidiabetes Agent, in Healthy Male Subjects

Abstract: The incidence of type 2 diabetes mellitus is increasing worldwide. Several G-protein-coupled receptor agonists are being studied for their efficacy as antidiabetes agents. JNJ-38431055 is a novel, potent, and orally available selective agonist of the glucose-dependent insulinotropic (GPR119) receptor. Double-blind, randomized, placebo-controlled studies were conducted to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of single oral doses of JNJ-38431055 (2.5-800 mg) in healthy male v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…These GPR119 agonists induced GSIS from pancreatic β-cells only under high-glucose conditions and displayed in vivo activity. JNJ-38431055 from Johnson & Johnson progressed to clinical trials with positive results but was terminated shortly afterwards, presumably because of subpar performance in the trials [31] . GSK-1292263 by GlaxoSmithKline has also completed Phase 2 clinical trials and was reported to be well-tolerated in preliminary findings [32] .…”
Section: Discussionmentioning
confidence: 99%
“…These GPR119 agonists induced GSIS from pancreatic β-cells only under high-glucose conditions and displayed in vivo activity. JNJ-38431055 from Johnson & Johnson progressed to clinical trials with positive results but was terminated shortly afterwards, presumably because of subpar performance in the trials [31] . GSK-1292263 by GlaxoSmithKline has also completed Phase 2 clinical trials and was reported to be well-tolerated in preliminary findings [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently no specific GPR119 antagonists are commercially available however studies have shown that GLP-1 receptor antagonist exendin (9-39) reduces glucose lowering ability of AR-231453 in mice (Chu et al, 2008;Flock et al, 2011). Clinical trials with GPR119 agonists namely JNJ-38431055 have shown therapeutic potential that may be augmented with the administered DPP-IV inhibitor (Katz et al, 2011(Katz et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…GPR119 agonism increases the release of incretin hormones and insulin from enteroendocrine and pancreatic beta cells which may underlie these beneficial effects (Chu et al, 2007;Gao et al, 2011;Lauffer et al, 2009). As a result of these advantageous effects GPR119 agonists have recently progressed to clinical trials (Katz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%